2021
DOI: 10.1101/2021.09.12.459881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An almost nontoxic tetrodotoxin analog, 5,6,11-trideoxytetrodotoxin, as an odorant for the grass puffer

Abstract: Toxic puffers contain the potent neurotoxin, tetrodotoxin (TTX). Although TTX is considered to serve as a defense substance, previous behavioral studies have demonstrated that TTX (extracted from the ovary) acts as an attractive pheromone for some toxic puffers. To determine the putative pheromonal action of TTX, we examined whether grass puffers (Takifugu alboplumbeus) can detect TTX using electrophysiological, morphological, and behavioral experiments. Electroolfactogram results suggest that the olfactory ep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Previous studies reported that TTX attracts tiger puffer ( T. rubripes , Okita et al, 2013; Saito et al, 2000) and grass puffer ( T. alboplumbeus , Matsumura,1995; Noguchi et al, 2021). These puffers live in the seawater, but the green spotted puffer lives in brackish water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that TTX attracts tiger puffer ( T. rubripes , Okita et al, 2013; Saito et al, 2000) and grass puffer ( T. alboplumbeus , Matsumura,1995; Noguchi et al, 2021). These puffers live in the seawater, but the green spotted puffer lives in brackish water.…”
Section: Discussionmentioning
confidence: 99%
“…Saito et al (2000) also reported that juvenile tiger puffers ( T. rubripes ) were attracted to TTX, and Okita et al (2013) reported that nose ablation eliminated the attractions of tiger puffers to TTX. Our electrophysiological and behavioral study has recently shown that an almost nontoxic TTX analog, 5,6,11-trideoxyTTX, acts as an olfactory chemoattractant for grass puffers (Noguchi et al, 2021). However, these studies have only been conducted on toxic puffers of the genus Takifugu .…”
Section: Introductionsmentioning
confidence: 99%